Living with Diabetes: Putting Together an Emergency Preparedness Plan - Nancy J. Gal (EDIS)
People with diabetes need to prepare in advance by having a plan and supply kit ready in the event of an emergency. This 3-page fact sheet describes key concerns that should be considered when developing an emergency plan and putting together a supply kit and lists the things that should be included in the supply kit. Written by Nancy J. Gal and published by the UF Department of Family Youth and Community Sciences, April 2012.